ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS SEBAGAI ALAT PENGENDALIAN INTERNAL - Muhamad Rifaldi (Jurnal Ilmu Akuntansi, 2021)
In the era of globalization, competition in the business world is getting tighter, with many companies that have entered people's lives. The increasingly widespread development of the business world today requires the development of a new accounting information system to meet the needs of better information. In addition, many companies are experiencing a decline in sales. For example, half of the trading companies experienced a decline in sales due to the unstable economy of the Indonesian people due to the pandemic. Similarly, companies engaged in the sale of vehicles were also affected, because the Indonesian Motorcycle Industry Association (AISI) reported that the volume of motorcycle sales distributed in October had decreased compared to the previous months. AISI data noted that there were 317,830 motorcycles distributed last October. Its volume fell 16.85% on a monthly basis compared to the previous month. With that accounting information system is needed, including sales accounting information systems and cash receipts, sales accounting information systems and cash receipts are part of an accounting information system that explains how to carry out sales procedures from receiving orders to receiving cash on sales. This study aims to find out how the company runs an accounting information system for sales and cash receipts, and the results of the research show that the companies that have been researched are in accordance with SOPs and using the right system. the sales activity in this study has used a qualitative approach descriptive method. Therefore, the use of accounting information systems sales and cash receipts is very instrumental and has a positive influence on the company's internal.